2020
DOI: 10.4293/jsls.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Surgery for Median Arcuate Ligament Syndrome

Abstract: Background: Compression of the celiac artery by the median arcuate ligament results in median arcuate ligament syndrome (MALS). Using a consecutive cohort of patients with MALS, this study evaluated the efficacy and safety of robotic median arcuate ligament release (MALR). Methods: A retrospective chart review was performed on patients who underwent robotic MALR from August 2012 to April 2018. Patient workup included history and physical examination, mesenteric Doppler ultrasound, and CT (Computed Tomography) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…MALS, also known as Dunbar syndrome or celiac artery compression syndrome, typically presents as a vague constellation of abdominal symptoms [5][6][7]. In a study of 36 patients with MALS, 94% reported abdominal pain, 80% reported postprandial pain, 56% reported nausea and vomiting, 50% experienced weight loss, and only 8% stated they had abdominal pain triggered by exercise [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MALS, also known as Dunbar syndrome or celiac artery compression syndrome, typically presents as a vague constellation of abdominal symptoms [5][6][7]. In a study of 36 patients with MALS, 94% reported abdominal pain, 80% reported postprandial pain, 56% reported nausea and vomiting, 50% experienced weight loss, and only 8% stated they had abdominal pain triggered by exercise [8].…”
Section: Discussionmentioning
confidence: 99%
“…The mainstay treatment for MALS is surgical decompression by dividing the fibers compressing the celiac trunk. Open and laparoscopic techniques of median arcuate ligament release have been considered the standard operation, but new robotic approaches have gained popularity in recent years [ 6 ]. Some alternative procedures will also remove the celiac plexus [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Robotic approaches to median arcuate ligament release offer enhanced 3D visualisation, improved stability and ergonomics, and increased ability to operate in more confined spaces, and the results have been promising with comparable short and intermediate term outcomes to laparoscopic approaches. 10,11 The short-term results of laparoscopic versus open, as well as ligament release alone versus combined with coeliac artery manipulation, are comparable, but there is again insufficient evidence to determine assess recurrence or restenosis. 7 This is further compounded by the fact that the pathophysiology behind MALS remains poorly understood, and so the potential placebo effect remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 4% of patients had no symptom resolution and 24% had symptom recurrence after an initial period of symptom resolution. The authors concluded that robotic MALR is a safe option for treatment of MALS with high-response rates [65].…”
Section: Median Arcuate Ligament Releasementioning
confidence: 97%